Por que sou rondoniano - Gomes, Mércio Pereira (Estudos Avançados, 2009)
This paper reviews the life and work of Brazilian Indianist Marshall Cândido Rondon. Rondon's life is marked by a profound dedication to the Brazilian Indian cause and to instilling in Brazilians a respect for Indian peoples. He influenced the Brazilian government in shaping a policy of protecting, assisting, and helping Indian peoples retain cohesive, self-determined societies. He also encouraged Indians to project their destinies onto a larger political context. The paper follows Rondon during his days as a cadet in the Military School; as a devout member of the Church of the Positivist Apostolate; as commander of the Rondon Expedition (1907-1930), which stretched the telegraph from Cuiabá to Porto Velho; and especially as the founder and leader of the Indian Protection Service (1910-1967). The Indian Protection Service is the precursor to today's National Indian Foundation (Funai), founded in 1967). Rondon is the creator of the expression "Die if you must, never kill" which, since 1910, has served as the motto for many of the Brazilian indianists who made the first contacts with Indian peoples. Many of them died in service for the Indian cause, demonstrating the high purpose of this new kind of humanistic vision. The Indian policy established by Rondon has experienced ups and downs throughout the last 100 years. Indeed, several Indian tribes became extinct and many lost their lands in the 20th Century. However, of the more than 220 tribes that survive today the vast majority are growing in numbers, have had most of their lands demarcated (amounting to 13% of the Brazilian territory) and are conquering space in the Brazilian cultural-political panorama.